Effect of a single immersion in cold water below 4 °C on haemorheological properties of blood in healthy men - Teległów, Aneta; Genc, Hatice; Cicha, Iwona (Scientific Reports, 2024)
Cold water immersion (CWI) involves rapid cooling of the body, which, in healthy individuals, triggers a defence response to an extreme stimulus, to which the body reacts with stress. The aim of the study was to determine the effect of CWI on hemorheological blood indicators. The study group consisted of 13 young males. Blood samples were collected before and after CWI. The assessed parameters included the complete blood count, fibrinogen, hs-C-reactive protein (CRP), proteinogram, and blood rheology factors, such as erythrocyte elongation index (EI), half-time of total aggregation, and aggregation index. Additionally, the effect of reduced temperature on primary human vascular endothelium was investigated in vitro. CWI resulted in the decrease of body temperature to 31.55 ± 2.87 °C. After CWI, neutrophil count and mean corpuscular volume (MCV) were significantly increased in the study group, while lymphocyte count was significantly decreased. Significantly higher levels of total blood protein and albumin concentration were detected after the immersion. Among hemorheological characteristics, erythrocyte EIs at shear stress values ranging from 2.19 to 60.30 Pa were significantly lower after CWI. No significant changes in other rheological, morphological or biochemical parameters were observed. In vitro, human umbilical vein endothelial cells responded to 3 h of temperature decrease to 25 °C with unchanged viability, but increased recruitment of THP-1 monocytic cells and changes in cell morphology were observed. This was the first study to evaluate the effect of single CWI on rheological properties of blood in healthy young men. The results indicate that a single CWI may increase blood protein concentrations and worsen erythrocyte deformability parameters.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Blood rheology; Cold water immersion (CWI); Endothelial cells; Erythrocytes; Low temperature